Literature Review: Peran Bahasa Arab Dalam Pembentukan Identitas Sosial dan Budaya Masyarakat Arab - Mardiyah, Ainun; Erlina, Erlina; Hijriyah, Umi; Koderi, Koderi; Rafli, Zaenal (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to examine the strategic role of the Arabic language in shaping the social and cultural identity of Arab society. The main focus of this review is how Arabic functions as a representation of social identity, a medium for preserving cultural values, and a means of forming religious identity and collective solidarity among Muslims. The method used is qualitative research based on a literature review, analyzing various scientific sources including journals, books, and articles published within the last five years. Data were collected through library research from national and international academic databases, then analyzed thematically through data reduction, categorization, and synthesis processes. The results indicate that Arabic not only serves as a communication tool but also as a symbol of collective identity that binds social structures, cultural values, and religious unity within Arab society. Arabic plays a fundamental role in maintaining cultural continuity and spirituality, while also acting as a means of social integration within Arab communities and the global Muslim ummah.